O avesso do glamour: um estudo do trabalho dos estilistas/designers de moda - Voltarel, Amanda Coelho Martins (2020)
This thesis aims to understand the particularities of the creative work of fashion stylists, or also called fashion designers. To this end, we conducted semi-structured interviews with workers engaged in different activities in the area of fashion, with a selection of training in fashion courses for all respondents. The data obtained from the interviews and the bibliographic research allowed us to understand how these workers are incorporated into the labor market, their activities, work experiences, the importance of creativity, the search for status, and the importance of recognition. We chose to interview designers who are not part of the mainstream activity marked by the glamor of parties and fashion shows, but rather its “reverse” world, the daily life of those engaged in fashion production, particularly, the clothing sector. We have developed the argument that the fashion world is seen as a space of appearances that conveys the idea of glamor. Designers in this field expect status and recognition, but find the “reverse” of glamor in working relationships, low wages, informality, adversity in entering the labor market, activities that do not match workers’ education, frustrations and disenchantments with the occupation. What we call “reverse glamour” is the creation of a category of workers, the stylists, who are a reworked version of the all-in-one fashion creator, the tailor and the seamstress. Wrapped in a glamor of the fashion world, they find its “reverse” in the job market.